Development of the embryonic heat shock response and the impact of repeated thermal stress in early stage lake whitefish (Coregonus clupeaformis) embryos. (October 2017) - Whitehouse, Lindy M.; McDougall, Chance S.; Stefanovic, Daniel I.; Boreham, Douglas R.; Somers, Christopher M.; Wilson, Joanna Y.; Manzon, Richard G.
Abstract: Lake whitefish ( Coregonus clupeaformis ) embryos were exposed to thermal stress (TS) at different developmental stages to determine when the heat shock response (HSR) can be initiated and if it is altered by exposure to repeated TS. First, embryos were subject to one of three different TS temperatures (6, 9, or 12 °C above control) at 4 points in development (21, 38, 60 and 70 days post-fertilisation (dpf)) for 2 h followed by a 2 h recovery to understand the ontogeny of the HSR. A second experiment explored the effects of repeated TS on the HSR in embryos from 15 to 75 dpf. Embryos were subjected to one of two TS regimes; +6 °C TS for 1 h every 6 days or +9 °C TS for 1 h every 6 days. Following a 2 h recovery, a subset of embryos was sampled. Our results show that embryos could initiate a HSR via upregulation of heat shock protein 70 ( hsp70 ) mRNA at all developmental ages studied, but that this response varied with age and was only observed with a TS of +9 or +12 °C. In comparison, when embryos received multiple TS treatments, hsp70 was not induced in response to the 1 h TS and 2 h recovery, and a downregulation was observed at 39 dpf. Downregulation of hsp47 and hsp90α mRNA was also observed in early age embryos. Collectively, these data suggest that embryos are capable of initiating a HSR at early age and throughout embryogenesis, but that repeated TS can alter the HSR, and may result in either reduced responsiveness or a downregulation of inducible hsps . Our findings warrant further investigation into both the short- and long-term effects of repeated TS on lake whitefish development. Highlights: Lake whitefish can initiate a heart shock response early in and throughout embryogenesis. Lake whitefish can up-regulate multiple heat shock proteins. Heat shock protein expression patterns vary with developmental age. Repeated thermal stress events can attenuate the heat shock response in lake whitefish embryos. Lake whitefish embryos have a plastic heat shock response.